2015
DOI: 10.1093/jscr/rjv078
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall necrotising fasciitis secondary to fish bone ingestion

Abstract: Abdominal wall necrotising fasciitis secondary to fish bone ingestion is extremely rare. We present a case of ingested fish bone complicated with self-sealing small bowel perforation and abdominal wall necrotising fasciitis. Following principles of necrotising fasciitis, a high index of suspicion led to early diagnosis and early treatment. The patient enjoyed a good recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Moreira et al [4], reported perirectal abscess caused by a chicken bone, but extensive NF caused by bowel perforation is still rare. In fact, the incidence of gastrointestinal perforation among foreign body ingestion cases is reported to be less than 1% [5]. When bowel perforation does occur, it can cause abscess formation due to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreira et al [4], reported perirectal abscess caused by a chicken bone, but extensive NF caused by bowel perforation is still rare. In fact, the incidence of gastrointestinal perforation among foreign body ingestion cases is reported to be less than 1% [5]. When bowel perforation does occur, it can cause abscess formation due to infection.…”
Section: Introductionmentioning
confidence: 99%